Finnes det en ordbokkritikk for redaksjonssjefer? - Eek, Øystein (LexicoNordica, 2003)
Is there a dictionary criticism for publishers, a dictionary criticism that can be of as much help as possible to publishers? As responsible publishers, we are forced to make a realistic view on what can be done with our recently published projects, when we are confronted by the critics' analysis of linguistic and lexicographical weaknesses. Academic dictionary criticism tends, of course, to focus on lexicographic and linguistic problems. A lot of useful (and free) advice is given to the authors and editors. However, the criticism would be even more relevant to publishers if the critics more often explicitly take into account the general economic conditions for dictionary publishing in small markets and for time the team are allowed to spend on a project. I hopethat competent lingui sts and lexicographers will make some efforts to analyse and discuss dictionaries in newspapers and magazines, as a means to enlarge the focus on dictionaries in our society.